Femtosecond laser direct inscribed 45° tilted fiber grating for a net-normal-dispersion mode-locked Er-doped fiber laser - Huang, Zinan; Huang, Qianqian; Theodosiou, Antreas; Kalli, Kyriacos; Li, Shaoying; Chen, Na; Chen, Tao; Mou, Chengbo (My University, 2021)
The application of a femtosecond laser direct inscribed 45° tilted fiber grating (TFG) in a net-normal-dispersion mode-locked Er-doped fiber laser, as an in-fiber polarizer, has been systematically studied. The 45° TFG with a grating length of ~ 12.6 mm and a grating period of ~ 2.2 μm has a polarization dependent loss of ~ 9.8 dB and supports various types of dissipative soliton (DS) outputs. The achieved single DS mode-locked pulse centered at 1570.55 nm has a 3 dB bandwidth of 15.64 nm and a pulse duration of ~ 4.68 ps. By simply employing a section of single-mode fiber, the output pulse duration can be dechirped to ~ 250 fs. The fundamental repetition rate is 25.47 MHz and the maximum pulse output power is 24.04 mW. By appropriately adjusting the intra-cavity polarization states and increasing the pump power, the bound-state DS, as well as a harmonic mode-locked DS, can be generated. The bound-state pulse is composed of two identical DS pulses with a temporal interval of ~ 26.27 ps. The second- and third-order harmonic mode-locked DS pulses with repetition rates of 50.93 MHz and 76.40 MHz are obtained for pump powers of 298 mW and 528 mW, respectively. Our results indicate that the feasibility and versatility of the femtosecond laser inscribed 45° TFG to realize nonlinear polarization evolution mode-locking in various operation regimes. Combined with the flexibility of the femtosecond laser direct inscription technique, such a 45° TFG paves a promising route for the development of robust, compact and high-energy ultrafast all-fiber lasers.
Keywords: Tilted fiber Bragg grating; Femtosecond laser inscription; Mode-locked fiber laser; Nonlinear polarization evolution; Dissipative soliton